Development and Characterization of Magnetic Carbon Foam from Starch and Ferromagnetic Fillers - Zainal Abidin, Muhamad Darwish Abidin; Mohamed Hatta, Mohamed Nasrul (Research Progress in Mechanical and Manufacturing Engineering, 2025)
Magnetic carbon foam were prepared using tapioca starch, iron oxide, cobalt ferrite, and sodium bicarbonate by applying the process of mixing, foaming, drying, and cabonization. The aim of this study is to synthesize magnetic carbon foam using different concentrations of ferromagnetic powder in carbon foam. To characterize the physical, structural, mechanical and magnetic properties of magnetic carbon foam. The physical properties of the material have been identified through density and porosity testing. The compression testing was conducted by Universal Testing Machine (UTM) to determine the mechanical properties of magnetic carbon foam. The microstructure characterization was determined by Scanning Electron Microscopy (SEM) analysis and X-Ray diffraction (XRD) analysis. Subsequently, the magnetic properties of the material was analyzed using magnet bar.